Modelling and Forecasting of Area, Production and Productivity of Tomatoes in Haryana and India - Nimbrayan, Parveen Kumar; Jaslam, P K Muhammed; Chandanshive, Aniket (Indian Journal of Extension Education, 2022)
An effort was made to investigate the behaviour of the area, production and productivity of tomato crop in the Haryana and India. For the purpose modelling and forecasting, linear trend, exponential trend, quadratic trend, S-curve trend, ARIMA modelling techniques were used and analysed the available information from 1991 to 2018. The results show that there will not be a significant increase in tomato productivity in Haryana, but it will raise yield in India. The total production of tomatoes in Haryana will be 1029 thousand tons by 2024 and the current production (2018-19) is 643.55 thousand tons and an increase of 4043 tons can be achieved in 2024 in India. It is noteworthy that although the area under tomatoes will increase in the near future in Haryana, but productivity remains the same. Productivity in India may increase in the coming years, although the area under cultivation remains the same.